Point-Of-Care Testing: The Ultrasonographic Evaluation of Non-Pregnant and Early Pregnant Mares - Pérez, Jeff (Spei Domus, 2019)
Introduction: The ultrasonographic evaluation of the reproductive tract in mares is one of the most reliable procedures for the diagnosis and monitoring of pregnancy. This tool has the ability to predict the potential impact that some diseases have on the quality and reproductive health of mares. Objective: To describe an appropriate approach to recognize the points of care testing in the ultrasonographic evaluation of pregnant and non-pregnant mares. Method of characterization: The POC (Point-of-Care Testing) are a series of criteria designed to provide quick results allowing a relative autonomy by the observer. Discussion: By definition, a POC test must be available for use by the patient and with the versatility of obtaining useful results for clinical decision making immediately. Conclusion: The importance of ultrasound in the gynecological and obstetric evaluation of the mare, highlights the importance of considering the points of attention of the test in the ultrasonographic examination of the reproductive system of the mares.